ON THE USE OF SOUND SPEED FOR EVALUATION OF THE PERFORMANCE OF LIQUID ULTRASONIC FLOW METER IN ZERO FLOW CONDITIONS - Lima, P. A. S. O.; Franco, L. G.; Ramos, R. (Revista de Engenharia Térmica, 2023)
At present, ultrasonic flow meters have become well known in custody transfer applications in the petroleum industry. Since facilities for calibration of these meters are costly and limited, methods for performance verification in zero flow conditions have been developed. However, for liquid measurement, a method of zero flow verification is not available yet. In this context, this study presents a new method for zero flow test in liquid ultrasonic flow meters, using a highly accurate instrument as a reference for sound speed. The aim is to evaluate the performance, of a multipath liquid ultrasonic flow meter under different pressures and temperatures, by comparing the calculated sound speed with the result from the reference instrument. Additionally, transit time measurement is also verified in order to account for systematic errors. The experiments were conducted with two test fluids: water and mineral oil, with a maximum deviation of 0.25% during comparison. On the other hand, performing a transit time analysis indicates the presence of systematic errors, meaning that transit times can be adjusted in order to improve the performance of the flow meter. Furthermore, a factorial design is performed to investigate the effect of pressure and temperature, indicating a minimal pressure effect on sound speed when compared to the temperature effect.